Extending teaching and learning initiatives in the cross-disciplinary field of biotechnology : final report. - Hine, Damian; Barnard, Ross; Rifkin, Will; Bridge, Wallace; Franco, Chris; Schmidt, Lisa; MacKinnon, Phillip (Carrick Institute for Learning and Teaching in Higher Education, 2008)
The purpose of this scoping study has been to identify gaps and opportunities for biotechnology learning and teaching in Australia and to discover pathways to enhance the quality of the curriculum in biotechnology and biotechnology-related programs across the higher education sector. Two essential features impact the complexity of this task: 1. Biotechnology is not a single discipline, but a composite of a range of disciplines, employed and integrated in differing combinations according to scientific need, with the aim of developing and delivering products of value. 2. Biotechnology is applied and therefore requires close consideration - now and into the future - of technological trends and trajectories, industry needs, skills and knowledge sets available to programs, specific regional strengths, and of its international nature. [p.4]